The Effect of Rehabilitative Punishments on Juvenile Crime and Labor Market Outcomes - Kristiina Huttunen; Sari Pekkala Kerr; Ville Mälkönen (Institute for the Study of Labor (IZA), 2014)
This paper estimates the effect of a rehabilitative punishment on the post-release outcomes of juvenile criminals using a unique Finnish data set on sentences and punishments merged with the longitudinal population census for 1990-2007. The rehabilitative program was aimed at improving the social skills and labor market attachment of young offenders aged 15 to 17. A variety of research designs are used to isolate the effect of the juvenile punishment and to control for observable characteristics of the young offenders. The juvenile punishment experiment was initially conducted in certain criminal courts only and was applicable for youths aged under 18, giving rise to a differences-in-differences and triple differences setup. The juvenile punishment reduced reoffending during the year immediately after sentencing, but had no long-term effect on reoffending nor on labor market outcomes.
Keywords: K14; K42; J29; 330; juvenile crime; punishments; rehabilitation; recidivism; earnings; employment